Hold Back or Held Back? The Roles of Constraint Mitigation and Exchange Diffusion on Power "Nonuse" in Buyer–Supplier Exchanges. Issue 2 (10th March 2017) - Crook, T. Russell; Craighead, Christopher W.; Autry, Chad W.
Abstract : Research on the use of power in buyer–supplier exchanges often derives insights from resource dependence theory to explain how power‐advantaged firms leverage their strength. Yet, when power‐advantaged firms should not—or cannot—use their power is less understood. To explain why firms should not use their power advantages, we put forth the concept of constraint mitigation, whereby firms relinquish power in mutually dependent contexts. To explain why firms cannot use their power advantages, we draw on insights from resource orchestration theory to put forth the concept of exchange diffusion . Exchange diffusion occurs when firms have not effectively structured and bundled a resource—in this case power. Thus, we theorize that exchange diffusion in power‐advantaged firms will limit their ability to use their power. Furthermore, and perhaps less intuitively, we argue that diffusion in weaker firms will also limit the ability of the stronger firm to use its power. In other words, we theorize that exchange diffusion "disarms" the stronger firm—regardless of whether self‐ or partner‐inflicted. Our key contribution is to offer theorizing centered on power nonuse. We also advance a theory of exchange diffusion, which could significantly augment our understanding of buyer–supplier exchanges.